Stabilization of Expansive Clay Using Volcanic Ash - Svetlana Melentijević; Aitor López Marcos; Roberto Ponce; Sol López-Andrés (Geosciences)
Considering the increasing requirements for the recovery of different natural and industrial waste materials, the application of volcanic ash as an alternative sustainable binder to traditionally employed lime and cement is proposed for soil stabilization for geotechnical engineering purposes, thus providing a reduction in carbon emissions. Soil stabilization was performed on natural clays with very high swelling potential, i.e. those classified as inadequate for reuse as a building material for geotechnical purposes. A mineralogical and chemical characterization of raw materials was carried out prior to the performance of different geotechnical laboratory tests, i.e., testing Atterberg limits, compaction, swelling potential, compressibility and resistance parameters over naturally remolded clay and soil mixtures with different binders. The swelling potential was reduced with an increase in the amount of applied binder, necessitating the addition of 10, 20, and 30% of volcanic ash compared to 3% lime, 3% cement and 5% lime, respectively, for a similar reduction in swelling potential. An investigation of the resistance parameters for soil mixture specimens that provided a suitable reduction in swelling potential for their reuse was performed, and a comparison to the parameters of naturally remolded clay was made.